Targeting type I interferons in systemic lupus erythematous - Bruera, Sebastian; Chavula, Thandiwe; Madan, Riya; Agarwal, Sandeep K. (Frontiers in Pharmacology, 2023)
Systemic lupus erythematosus (SLE) is a complex autoimmune disease with systemic clinical manifestations including, but not limited to, rash, inflammatory arthritis, serositis, glomerulonephritis, and cerebritis. Treatment options for SLE are expanding and the increase in our understanding of the immune pathogenesis is leading to the development of new therapeutics. Autoantibody formation and immune complex formation are important mediators in lupus pathogenesis, but an important role of the type I interferon (IFN) pathway has been identified in SLE patients and mouse models of lupus. These studies have led to the development of therapeutics targeting type I IFN and related pathways for the treatment of certain manifestations of SLE. In the current narrative review, we will discuss the role of type I IFN in SLE pathogenesis and the potential translation of these data into strategies using type I IFN as a biomarker and therapeutic target for patients with SLE.